III. Fund for purchase of Oliver Sheppard's statue 'Inis Fáil', - Burke, John L. (John Leo), 1888-1959 (1937)
Correspondence, receipts, subscriptions, publicity material and accounts relating to the purchase of the statue for the Municipal Gallery of Modern Art, Dublin [Hugh Lane Municipal Gallery of Modern Art].